Early vestibular and visual dysfunction predicts prolonged symptomatology following paediatricpediatric concussion. Issue 11 (25th May 2017) - Master, Christina L; Grady, Matthew F; Storey, Eileen; Podolak, Olivia; Lockyer, Julia; Wiebe, Douglas
Abstract : Objective: Vestibular and visual dysfunction, including accommodation disorder, symptoms with vestibular ocular reflex (VOR) testing, or receded near point of convergence, are common following concussion and have been associated with prolonged concussion symptomatology. The objective of this study was to determine whether vestibular and visual information contributed significantly to a model predicting the likelihood of having persistent concussion symptoms at 28 days after injury. Design: Retrospective cohort study Setting: Sports medicine concussion program within a large regional paediatric healthcare network. Participants: 274 consecutive patients aged 3-18 years with the diagnosis of concussion seen in the concussion program Independent Variables: Standard demographic and clinical data, as well as vestibular and visual examination findings at presentation Outcome measures: Symptom recovery from concussion, defined as a symptom score=0 on the Post Concussion Symptom Scale at 28 days Main results: Study subjects were 3–18 years (median=14), presenting a median of 14 days from injury. Applying a stepwise regression approach using traditional demographic and clinical variables (age, gender, past medical history, symptoms and balance testing) as well as information from vestibular and visual testing, we found that VOR testing is a statistically significant component (p=0.02) of the final predictive model. Furthermore, in the subset of patients presenting within 14 days of injury, positive VOR testing (p=0.02) and vision problems (p=0.01) significantly contribute to predicting ongoing symptoms at 28 days. Conclusions: Symptoms with VOR testing and vision problems upon presentation within 14 days of injury contributed significantly to the prediction model for prolonged symptoms following concussion and warrant further study. Competing interests: None.